THE USE OF DIRECT OBSERVATION TO EVALUATE THE DEGREE OF VISUAL COMFORT IN THE LIBRARY OF GUELMA UNIVERSITY - Ismahane Haridi,; Messaoud Aiche,; Abdeldjalil Hamdaoui,; Ahmed Mounir Ansar, (International Journal of Innovative Technologies in Social Science, 2025)
In libraries, the integration of natural light through illuminated spaces has long been a hallmark of aesthetically pleasing and comfortable environments, fostering an enjoyable reading experience without glare. This practice has been deeply rooted in architectural tradition for centuries. In reading rooms, proper lighting is essential for effectively supporting reading activities. The study employs various methods to collect data, including both data analysis and observation. For our research, we will specifically use observation as the primary investigative technique. This approach will allow us to analyze photographs taken in the library. The objective of this study is to assess visual comfort in relation to the quality of natural light in the reading room of the Guelma library, using an evaluation grid applied on two different days, one in winter and one in summer. The results will reflect the level of discomfort or comfort experienced during reading activities within the room. The grid will help explain the critical role of observation in this evaluation and provide insight into the current lighting conditions, along with the sensory experience related to the required visual comfort standards.